2011
DOI: 10.2135/cropsci2011.01.0046
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Characterization and Molecular Mapping Pse‐2 Gene for Resistance to Halo Blight in Common Bean

Abstract: Pseudomonas syringae pv. phaseoticola (Burkholder) Young et al. {Psp) causes halo blight, which is a serious bacterial disease of common bean {Phaseolus vulgaris L.). Several resistance (R) genes have been discovered in host differential cultivar ZAA 12. Our objectives were to further characterize and enable marker-assisted selection (MAS) of the Pse-2 gene in ZAA 12 purJDorted to have broad effect against multiple Psp races. A recombinant inbred population, ZAA 12 X 'Canadian Wonder', was challenged by the ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
35
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 22 publications
2
35
0
Order By: Relevance
“…The severe hypersensitive reaction to Race 3 (conferred by Pse-3 ) co-segregated with the I gene locus on Pv02 (48.398–48.534 Mb) (Figure 2C, right graph; Table S1), which is consistent with previous observations (Teverson, 1991; Miklas et al, 2011, 2014). Linked markers show a pattern of segregation distortion in favor of the parent possessing the resistance allele similar to that observed in the RC population (described below).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…The severe hypersensitive reaction to Race 3 (conferred by Pse-3 ) co-segregated with the I gene locus on Pv02 (48.398–48.534 Mb) (Figure 2C, right graph; Table S1), which is consistent with previous observations (Teverson, 1991; Miklas et al, 2011, 2014). Linked markers show a pattern of segregation distortion in favor of the parent possessing the resistance allele similar to that observed in the RC population (described below).…”
Section: Resultssupporting
confidence: 90%
“…Instead, these races mapped the same QTL on Pv10 (3.411–3.457 Mb) that was detected with Races 2, 7, 8, and 9, while an additional QTL was detected with Race 3 on Pv02 (47.368–48.296 Mb). These QTL correspond to race-specific loci Pse-2 (conferring resistance to Races 2, 3, 4, 5, 7, 8, and 9) and Pse-3 (conferring resistance to Races 3 and 4) that were previously mapped in other bean lines (Miklas et al, 2011). This may indicate that CAL 143 contains an alternative race-specific resistance allele in the HB4.2 mapping interval that is tightly linked but functionally distinct from the race-nonspecific allele in PI 150414.…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…For the recombinant inbred population studied by Miklas et al (2011), complete cosegregation was observed for Pse-3 and the I gene, which conditions an immune response or temperature-dependent HR to Bean common mosaic virus (BCMV) and a temperature-independent HR to Bean common mosaic necrosis virus (BCMNV). For the recombinant inbred population studied by Miklas et al (2011), complete cosegregation was observed for Pse-3 and the I gene, which conditions an immune response or temperature-dependent HR to Bean common mosaic virus (BCMV) and a temperature-independent HR to Bean common mosaic necrosis virus (BCMNV).…”
mentioning
confidence: 99%
“…For the recombinant inbred population studied by Miklas et al (2011), complete cosegregation was observed for Pse-3 and the I gene, which conditions an immune response or temperature-dependent HR to Bean common mosaic virus (BCMV) and a temperature-independent HR to Bean common mosaic necrosis virus (BCMNV). Miklas et al (2011) identified Pse-2 as the second gene reported by Teverson (1991) in ZAA 12, in addition to Pse-3, which governed HR to Races 3 and 4. Miklas et al (2011) identified Pse-2 as the second gene reported by Teverson (1991) in ZAA 12, in addition to Pse-3, which governed HR to Races 3 and 4.…”
mentioning
confidence: 99%